Changes in egg quality traits during the last phase of production: is there potential for an extended laying cycle?. Issue 6 (1st November 2016) - Molnár, A.; Maertens, L.; Ampe, B.; Buyse, J.; Kempen, I.; Zoons, J.; Delezie, E.
Abstract: 1. A field study was conducted to investigate the deterioration of eggshell quality at the end of lay and examine the potential to extend the production cycle. A total of 1200 eggs were assessed originating from commercial farms in Belgium: eggs were random sampled at the collection belt at 57–65 weeks of age and at the end of the production cycle (74–92 weeks). 2. Based on a linear mixed model, egg quality was estimated for an average flock at 60 weeks of age and changes in quality traits were predicted until the end of the laying cycle. 3. Egg weight increased by 0.07 g every week from 60 weeks of age onwards and shape index decreased by 0.04 unit weekly ( P <  0.001). Haugh unit values decreased weekly by 0.38 units whereas relative yolk weight was unaffected after 60 weeks of age. Relative albumen weight showed a weekly increase of 0.02% and relative shell decreased by 0.02% weekly until the end of lay. 4. Shell quality traits were also influenced by age: shell index decreased by 0.013 g weekly, shell thickness was calculated to be 0.23 µm thinner every week, deformation increased by 0.06 µm weekly from 60 weeks to the end of the laying cycle. Variability of the deformation of eggs indicated more heterogeneous shell quality at the end of the production cycle. Dynamic stiffness increased from 60 weeks of age on. 5. Laying hens were depopulated on average at 80 weeks of age (varying from 74–92 weeks). Although ageing had a significant effect on most of the egg quality traits, egg quality was still acceptable at the end of lay, indicating the potential to extend the laying cycle.